2011
DOI: 10.1371/journal.pntd.0001262
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Genotyping of Human Giardia Isolates Suggests Limited Zoonotic Transmission and Association between Assemblage B and Flatulence in Children

Abstract: Background Giardia intestinalis is one of the most common diarrhea-related parasites in humans, where infection ranges from asymptomatic to acute or chronic disease. G. intestinalis consists of eight genetically distinct genotypes or assemblages, designated A–H, and assemblages A and B can infect humans. Giardiasis has been classified as a possible zoonotic disease but the role of animals in human disease transmission still needs to be proven. We tried to link different assemblages and sub-assemblages of G. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
112
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(140 citation statements)
references
References 44 publications
(76 reference statements)
25
112
1
2
Order By: Relevance
“…Evidence for strong LD between different kinds of markers is abundant in this species Monis et al, 2009), with 'assemblages', that are perfectly equatable to near-clades (Tibayrenc and Ayala, 2014b). Giardia assemblages (labelled A to G) exhibit a neat, but not strict, host specificity and some phenotypic differences, and are corroborated by MLEE and gene sequences (Cacci o and Ryan, 2008;Lasek-Nesselquist et al, 2009;Lebbad et al, 2011;Monis et al, 2009;Ortega-Pierres et al, 2009;Plutzer et al, 2010;Takumi et al, 2012;Xu et al, 2012). Additional subdivisions ('subassemblages') can be identified within the assemblages.…”
Section: Parasitic Protozoamentioning
confidence: 70%
“…Evidence for strong LD between different kinds of markers is abundant in this species Monis et al, 2009), with 'assemblages', that are perfectly equatable to near-clades (Tibayrenc and Ayala, 2014b). Giardia assemblages (labelled A to G) exhibit a neat, but not strict, host specificity and some phenotypic differences, and are corroborated by MLEE and gene sequences (Cacci o and Ryan, 2008;Lasek-Nesselquist et al, 2009;Lebbad et al, 2011;Monis et al, 2009;Ortega-Pierres et al, 2009;Plutzer et al, 2010;Takumi et al, 2012;Xu et al, 2012). Additional subdivisions ('subassemblages') can be identified within the assemblages.…”
Section: Parasitic Protozoamentioning
confidence: 70%
“…However, this is unsupported, since many long-term infections are suspected to represent either persisting abdominal symptoms elicited post-Giardia infection or reinfections (176,196,484). The fecal-oral route still remains the most important mode of infection (33), and various studies have found evidence of zoonotic transmission (89,118,237). The symptoms of giardiasis can be variable, but it presents mainly as acute or chronic diarrhea associated with abdominal pain, nausea, malabsorption, and weight loss.…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…En algunos estudios recientes se ha sugerido que esta especie debería considerarse como un complejo de especies cuyos miembros, aunque morfológicamente idénticos, presentan variaciones genéticas que han permitido dividirla en, al menos, ocho genotipos (del A al H) (4).…”
unclassified